(untitled) (Journal of the College of Basic Education, 2026)
The research addresses the lack of understanding regarding the relationship between sport confidence and psychological integration among fifth-grade preparatory students. The study aims to explore the extent of this relationship by developing two measurement scales, one for sport confidence and the other for psychological integration, and applying them to a sample of students from the literary branch at Al-Abrar Preparatory School for Boys. After establishing homogeneity within the sample and validating the scales through expert review, data were collected from a main group of 30 students following an initial pilot study involving 5 students. The statistical analysis revealed a positive correlation between sport confidence and psychological integration, indicating that students with higher levels of sport confidence tend to exhibit better psychological integration. The study concludes that enhancing sport confidence through active participation in physical education activities can contribute to students’ psychological development, and recommends that physical education teachers give greater attention to students’ psychological needs. The developed scales may also be applied to other student groups in future research .